2001
DOI: 10.1046/j.1461-0248.2001.00205.x
|View full text |Cite
|
Sign up to set email alerts
|

Trait variability and stress: canalization, developmental stability and the need for a broad approach

Abstract: Trait variability (particularly fluctuating asymmetry) may provide a general measure of environmental stress applicable across taxa but consistent empirical support is lacking. Historically, stress effects were considered to act independently on trait canalization, developmental noise and trait size. However, in trait comparisons these processes are often assumed to be associated. Here we reconsider this issue and implications for detecting stress effects using trait variability. Published studies that conside… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

2
55
0

Year Published

2004
2004
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 52 publications
(57 citation statements)
references
References 21 publications
2
55
0
Order By: Relevance
“…The relationship between DI and canalization is controversial similar to the relationship between DI and heterozygosity. Hoffmann and Woods (2001) found no general relationship between DI and canalization in a small review of the data available at the time. A later study, however, showed that such a relationship may be present for wing shape, as a significant correlation between DI and canalization was found for this trait, but not for wing size (Breuker et al 2006).…”
Section: Introductionmentioning
confidence: 94%
See 1 more Smart Citation
“…The relationship between DI and canalization is controversial similar to the relationship between DI and heterozygosity. Hoffmann and Woods (2001) found no general relationship between DI and canalization in a small review of the data available at the time. A later study, however, showed that such a relationship may be present for wing shape, as a significant correlation between DI and canalization was found for this trait, but not for wing size (Breuker et al 2006).…”
Section: Introductionmentioning
confidence: 94%
“…While phenotypic plasticity refers to the ability of a genotype to produce different phenotypes in different environments, canalization refers to the ability of different genotypes to produce the same phenotype in a given environment (Hoffmann and Woods 2001). The relationship between DI and canalization is controversial similar to the relationship between DI and heterozygosity.…”
Section: Introductionmentioning
confidence: 99%
“…The question of whether canalization ( 2 p) and DI (FA) are affected by different mechanisms has been doubted by several authors (Dworkin 2005;Willmore et al 2006), and supported by others (Hoffmann and Woods 2001;Rego et al 2006). However, no clear conclusion has been reached and the underlying genetic mechanisms of 2 p and FA have yet to be evaluated.…”
Section: Introductionmentioning
confidence: 99%
“…other insects), social insect sexuals from more stressful colonies would be predicted to show a smaller and more variable size (lower mean and higher coefficient of variation) (cf. for example, Imasheva et al 1997;Clarke 1998;Hoffmann and Schiffer 1998;Woods et al 1999; see also Hoffmann and Woods 2001). Also, the levels of fluctuating asymmetry (FA) (the random deviation in size of left and right sides of a bilateral trait), which is widely used as an estimator of developmental stability in the face of environmental stress (e.g.…”
Section: Introductionmentioning
confidence: 99%
“…Hoffmann and Woods 2001;Hogg et al 2001; see also Polak et al 2002). However, I incorporated FA analyses in my study to make it as inclusive as possible.…”
Section: Introductionmentioning
confidence: 99%